THE INFLUENCE OF FINANCIAL LITERACY, FINTECH ADOPTION, AND INVESTMENT PREFERENCES ON THE INVESTMENT BEHAVIOR OF MILLENNIALS IN JAKARTA IN THE DIGITAL BANKING ERA - Afifi, Zaenal; -, Riny; Silkfan, Rara (AKRUAL : Jurnal Akuntansi dan Keuangan, 2025)
This study examines the influence of financial literacy, fintech adoption, and investment preferences on the investment behavior of millennials in Jakarta during the digital banking era. Employing a quantitative research design, data were collected from 150 respondents using a structured questionnaire based on a Likert scale (1-5). The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) to evaluate both the measurement and structural models. The results reveal that financial literacy, fintech adoption, and investment preferences positively and significantly influence investment behavior. Among these factors, fintech adoption exerts the most substantial impact, underscoring the transformative role of technology in shaping investment decisions. The findings suggest that financial institutions and policymakers should prioritize financial literacy initiatives, foster fintech innovation, and develop personalized investment strategies to empower millennial investors. This study contributes to the growing body of literature on millennial financial behavior, offering actionable insights for stakeholders in the financial sector.